EMBEDDING ISLAMIC ETHICAL VALUES IN ENTREPRENEURIAL DECISION-MAKING: FROM SHARIA TO STRATEGY - Mochamad Sumpena (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This paper explores integrating Islamic ethical values into the decision-making process of entrepreneurs. It examines how Sharia principles, which govern Muslim behavior in personal and professional spheres, can be instilled in business strategy. By analyzing various entrepreneurial scenarios in Islamic contexts, this study highlights the potential benefits and challenges of incorporating ethical guidelines rooted in Islamic teachings. Furthermore, this paper provides insight into how Islamic values, such as fairness, transparency, and accountability, can influence decision-making strategies in a competitive business environment. This research contributes to the growing literature on Islamic entrepreneurship by proposing a framework for entrepreneurs to make ethically sound decisions that align with religious teachings and business success.